Kajian Literatur tentang Perkembangan Peserta Didik dalam Mendukung Keberhasilan Pembelajaran - Putri Husnul Khotimah (Al Fitrah: Journal Of Early Childhood Islamic Education, 2026)
Student development is an important aspect in the educational process because it affects learning outcomes and children’s overall growth. This study aims to analyze student development in physical,cognitive, social, and emotional aspects during the learning process. The study used a literature review method combined with descriptive quantitative analysis using developmental assesment categories BB, MB, BSH, and BSB. Dara were obtained from books, journal, and scientific articles related to child development and education from Google Scholar and Google Books. The results showed that appropriate learning stimulation can improve student development in various aspects. Most students were categorized in BSH and BSB levels. Therefore, teachers and parents need to provide effective learning stimulation according to children’s developmental stages.